Peru’s energy policy in the context of energy transition - I. A. Guliev; Yu. V. Solovova (Ибероамериканские тетради)
We examine the evolution of Peru’s energy strategy in the context of global energy transition trends. In the last decade, Peru’s energy sector has been actively developing due to an increase in domestic demand caused by the country’s economic growth. At the moment, the country is facing the task of expanding its energy system to ensure access to energy and at the same time its modernization in the context of the global climate agenda. The risks caused by climate change can have a significant negative impact on the ecosystem of Peru and pose serious threats to the future economic development of the country. Authors analyze the current state and prospects of the energy sector, which is the main engine of national economic growth and a significant factor for poverty eradication. We discuss the foundations of the state energy development strategy, the role of the climate agenda, and the specifics of renewable energy project regulation. Authors conclude that Peru has significant potential both in the field of traditional hydrocarbon energy, including LNGs, and in the field of clean energy. In addition to solar and wind power, Peru also has significant potential for the development of hydrogen and biomass energy. Of particular importance for the country is the gas industry, which has received a serious impetus for development in connection with the implementation of a major Camisea project. During the transition period, gas can partially replace the use of oil in industry, housing and electricity generation, thus contributing to the process of decarbonization. The choice of strategic priorities will determine the country’s energy architecture in the medium and long term.